The esteras [reed mats]. Weaving the memory of the popular city - Ramírez Corzo, Daniel (2024)
This article explores the role of esteras (reed mats) in the history and memory of Lima’s barriadas, in Peru. It analyzes how this material, fundamental in the initial occupation and construction of dwellings, has evolved, examining its trajectory in art, architecture, and social imaginaries, highlighting its potential as popular urban heritage. The research includes experimental projects to recontextualize esteras in public space. The authors propose that esteras can serve as a catalyst for social memory and identity in consolidated barriadas, transcending their original use to become a significant element in the production of popular public space and in the construction of a fairer urban memory.